Who's responsible for the care of women during and after a pregnancy affected by gestational diabetes?. (21st July 2014) - Wilkinson, Shelley A; Lim, Siew S; Upham, Susan; Pennington, Andrew; O'Reilly, Sharleen L; Asproloupos, Dino; McIntyre, H David; Dunbar, James A
Summary: Despite its increasing incidence and high conferred risk to women and their children, gestational diabetes mellitus (GDM) is managed inconsistently during and after pregnancy due to an absence of a systemic approach to managing these women. New guidelines for GDM testing and diagnosis are based on stronger evidence, but raise concerns about increased workloads and confusion in a landscape of multiple, conflicting guidelines. Postnatal care and long‐term preventive measures are particularly fragmented, with no professional group taking responsibility for this crucial role. Clearer guidelines and assistance from existing frameworks, such as the National Gestational Diabetes Register, could enable general practitioners to take ownership of the management of women at risk of type 2 diabetes following GDM, applying the principles of chronic disease management long term.